Cultivating pomegranate for prosperity - Kumar, R; Saroj, P L; Sharma, B D (Indian Horticulture, 2019)
Pomegranate has ability to withstand harsh climate and tolerate heat, drought and moisture deficit. The area under pomegranate cultivation in hot arid region is increasing at faster rate owing to its high demand, hardy nature, low maintenance cost, high yields and better storage quality. It has vast medicinal, nutritional value and one of the richest sources of antioxidants and also known as ‘super food’. It is processed into value added products such as juices, squash, jelly, anardana and mouth freshener. Development of improved varieties, standardization of agro-techniques suiting to arid environments and spread of canal irrigation has led to increase in area of pomegranate particularly in hot arid region of Bikaner, Jodhpur, Jaisalmer, Barmer, Shriganganagar and Hanumangarh districts of Rajasthan.